Computational Intelligence in Digital Forensics - Muda, A. K. (Springer, 2014)
Forensic Science has been around for quite some time. Although various forensic methods have been proved for their reliability and credibility in the criminal justice system, their main problem lies in the necessity of highly qualified forensic investigators. In the course of analysis of evidences, forensic investigators must be thorough and rigorous, hence time consuming. Digital Forensic techniques have been introduced to aid the forensic investigators to acquire as reliable and credible results as manual labor to be presented in the criminal court system. In order to perform the forensic investigation using Digital Forensic techniques accurately and efficiently, computational intelligence oftentimes employed in the implementation of Digital Forensic techniques, which has been proven to reduce the time consumption, while maintaining the reliability and credibility of the result, moreover in some cases, it is producing the results with higher accuracy. The introduction of computational intelligence in Digital Forensic has attracted a vast amount of researchers to work in, and leads to emergence of numerous new forensic investigation domains.